Le premier ministre sur le sentier de la guerre ou Le chien a deux queues - Szabó, Dávid (Linguistica (Ljubljana), 2018)
In this paper I analyse Hungarian political slang, or slang as it is used in Hungarian politics, especially as it appears in the pro-refugee campaign of a recently created mock party, the Hungarian Two-tailed Dog Party. While the Hungarian government, during its campaign against the relocation of refugees, used very few slang or colloquial terms, the language of the Two-tailed Dog Party is rich in slang words and neologisms. The analysis is mostly based on data gathered on the Internet in 2016-17.
Keywords: analiza diskurza; Madžarska; madžarščina; nekonvencionalni jezik; politični jezik